The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1980-65742013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Predição da potência aeróbia (VO2máx) de crianças e adolescentes em teste incremental na esteira rolante

Abstract: IntroduçãoO consumo máximo de oxigênio (VO 2 máx) juntamente com o limiar de lactato (LL) são considerados os melhores indicadores da aptidão aeróbia, sendo ambos amplamente utilizados para a predição da performance, para a avaliação dos efeitos do treinamento e identificação da adequada intensidade de esforço (BILLAT, 1996;BILLAT et al., 1999;NICHOLSON;SLEIVERT, 2001;BASSET;HOWLEY, 2000;PAPADOPOULOS et al., 2006). O VO 2 máx é uma medida que reflete a quantidade máxima de energia que pode ser produzida pelo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Comparing the obtained results with other papers where models were calculated only for males, it may be observed that the parameter value does not deviate significantly from the published results ( Table 6). The optimal model for males calculated in the study generated greater errors than the models presented by Machado and Demadai [67] (4.10 [mL•kg −1 •min −1 ]) and Bandyopdhyay [68] (1.41 [mL•kg −1 •min −1 ]). The error obtained is still smaller than the error generated using the Costa model [69]…”
Section: Discussionmentioning
confidence: 63%
“…Comparing the obtained results with other papers where models were calculated only for males, it may be observed that the parameter value does not deviate significantly from the published results ( Table 6). The optimal model for males calculated in the study generated greater errors than the models presented by Machado and Demadai [67] (4.10 [mL•kg −1 •min −1 ]) and Bandyopdhyay [68] (1.41 [mL•kg −1 •min −1 ]). The error obtained is still smaller than the error generated using the Costa model [69]…”
Section: Discussionmentioning
confidence: 63%
“…Maximal exercise tests (Bandyopadhyay, 2011;Machado & Denadai, 2013;Silva et al, 2012;Veronese da Costa et al, 2013). and sub maximal exercise tests (Billinger, Swearingen, McClain, Lentz, & Good, 2012;Tonis, Gorter, Vollenbroek-Hutten, & Hermens, 2012)are usually performed on a treadmill, ergometer or a track.…”
Section: Introductionmentioning
confidence: 99%